ANTHROPOLOGICAL LINGUISTICS IN THE CULTURAL CONTEXT - Gulchekhra Khazratova (Modern American Journals, 2025)
The article considers anthropolinguistics, anthropological linguistics as a branch of linguistics that studies the evolution of human thinking based on its reflection in the corresponding evolution of the language (primarily its vocabulary). The main reason for this section is the fact that the majority of cultural transformations, the history of human knowledge, and a lot of socially innovative.
Keywords: Anthropological linguistics, linguistic classifications, linguistic forms, linguistic structure, linguistic characteristics, ethnographic branches, visual perception.